Hierarchical star formation across the ring galaxy NGC 6503 - Gouliermis, Dimitrios A.; Thilker, David; Elmegreen, Bruce G.; Elmegreen, Debra M.; Calzetti, Daniela; Lee, Janice C.; Adamo, Angela; Aloisi, Alessandra; Cignoni, Michele; Cook, David O.; Dale, Daniel A.; Gallagher, John S.; et al. (Monthly notices of the Royal Astronomical Society, 2015)
We present a detailed clustering analysis of the young stellar population across the star-forming ring galaxy NGC 6503, based on the deep Hubble Space Telescope photometry obtained with the Legacy ExtraGalactic UV Survey. We apply a contour-based map analysis technique and identify in the stellar surface density map 244 distinct star-forming structures at various levels of significance. These stellar complexes are found to be organized in a hierarchical fashion with 95 per cent being members of three dominant super-structures located along the starforming ring. The size distribution of the identified structures and the correlation between their radii and numbers of stellar members show power-law behaviours, as expected from scale-free processes. The self-similar distribution of young stars is further quantified from their autocorrelation function, with a fractal dimension of ∼1.7 for length-scales between ∼20 pc and 2.5 kpc. The young stellar radial distribution sets the extent of the star-forming ring at radial distances between 1 and 2.5 kpc. About 60 per cent of the young stars belong to the detected stellar structures, while the remaining stars are distributed among the complexes, still inside the ring of the galaxy. The analysis of the time-dependent clustering of young populations shows a significant change from a more clustered to a more distributed behaviour in a time-scale of ∼60 Myr. The observed hierarchy in stellar clustering is consistent with star formation being regulated by turbulence across the ring. The rotational velocity difference between the edges of the ring suggests shear as the driving mechanism for this process. Our findings reveal the interesting case of an inner ring forming stars in a hierarchical fashion.
Gesehen am 31.08.2020